Missed low-grade infection in suspected aseptic loosening has no consequences for the survival of total hip arthroplasty: 173 patients followed for 6 to 9 years. (2nd November 2015) - Boot, Willemijn; Moojen, Dirk Jan F; Visser, Els; Lehr, A Mechteld; De Windt, Tommy S; Van Hellemondt, Gijs; Geurts, Jan; Tulp, Niek J A; Schreurs, B Wim; Burger, Bart J; Dhert, Wouter J A; Gawlitta, Debby; et al.
Abstract : Background and purpose — Aseptic loosening and infection are 2 of the most common causes of revision of hip implants. Antibiotic prophylaxis reduces not only the rate of revision due to infection but also the rate of revision due to aseptic loosening. This suggests under-diagnosis of infections in patients with presumed aseptic loosening and indicates that current diagnostic tools are suboptimal. In a previous multicenter study on 176 patients undergoing revision of a total hip arthroplasty due to presumed aseptic loosening, optimized diagnostics revealed that 4–13% of the patients had a low-grade infection. These infections were not treated as such, and in the current follow-up study the effect on mid- to long-term implant survival was investigated. Patients and methods — Patients were sent a 2-part questionnaire. Part A requested information about possible re-revisions of their total hip arthroplasty. Part B consisted of 3 patient-related outcome measure questionnaires (EQ5D, Oxford hip score, and visual analog scale for pain). Additional information was retrieved from the medical records. The group of patients found to have a low-grade infection was compared to those with aseptic loosening. Results — 173 of 176 patients from the original study were included. In the follow-up time between the revision surgery and the current study (mean 7.5 years), 31 patients had died. No statistically significant difference in the number of re-revisions was found between the infection group (2 out of 21) and the aseptic loosening group (13 out of 152); nor was there any significant difference in the time to re-revision. Quality of life, function, and pain were similar between the groups, but only 99 (57%) of the patients returned part B. Interpretation — Under-diagnosis of low-grade infection in conjunction with presumed aseptic revision of total hip arthroplasty may not affect implant survival.